DEVELOPING INTERACTIVE WRITING WORKSHEET DESCRIPTIVE TEXT TO PROMOTE HIGHER ORDER THINKING SKILL FOR EIGHT GRADE STUDENT AT MADRASAH TSANAWIYAH NEGERI 2 MEDAN - Firsty Azirila Putri; Rahmad Husein; Safrida Lubis (Universitas Negeri Medan, 2021)
Putri, Firsty Azirila. Registration Number: 2153121012. Developing Interactive Writing Worksheet to Promote Higher Order Thinking Skill for Eight Grade Student at Madrasah Tsanawiyah Negeri 2 Medan. English Education Program, Universitas Negeri Medan, 2020. The aimed of this study was to develop students’ interactive writing worksheet descriptive text to promote higher order thinking skill. This study was conducted by using Research and Development (R&D) through six stages: gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subject of the study was grade VIII at Madrasah Tsanawiyah Negeri 2 Medan. The instruments of the data collection were gathered by interview the teacher and giving the questionnaire. The study conducted interview to English teacher and giving the questionnaire to 35 respondents to get the students’ needs. The interview and questionnaire result proved that the students’ need English learning media which can motivate the students to understand about interactive writing worksheet descriptive text. The product had been validated by the experts namely English teacher and English lecturer. The product result was Interactive Writing Worksheet which had been modified to promote Higher Order Thinking Skill. The result of the experts’ validation showed that the media was appropriate to be used on the interactive writing worksheet by getting the average score is 4.5 categorized excellent.